Frequencies of 23 Functionally Significant Variant Alleles Related with Metabolism of Antineoplastic Drugs in the Chilean Population: Comparison with Caucasian and Asian Populations - Roco, Angela M.; Quiñones, Luis A.; Agúndez, José A.; García-Martín, Elena; Squicciarini, Valentina; Miranda, Carla E.; Garay, Joselyn; Farfán, Nancy; Saavedra, Iván N.; Caceres, Dante D.; Ibarra, Carol; Varela, Nelson M. (Frontiers in Genetics, 2012)
Cancer is a leading cause of death worldwide. The cancer incidence rate in Chile is 133.7/100,000 inhabitants and it is the second cause of death, after cardiovascular diseases. Most of the antineoplastic drugs are metabolized to be detoxified, and some of them to be activated. Genetic polymorphisms of drug-metabolizing enzymes can induce deep changes in enzyme activity, leading to individual variability in drug efficacy and/or toxicity. The present research describes the presence of genetic polymorphisms in the Chilean population, which might be useful in public health programs for personalized treatment of cancer, and compare these frequencies with those reported for Asian and Caucasian populations, as a contribution to the evaluation of ethnic differences in the response to chemotherapy. We analyzed 23 polymorphisms in a group of 253 unrelated Chilean volunteers from the general population. The results showed that CYP2A6*2, CYP2A6*3, CYP2D6*3, CYP2C19*3 and CYP3A4*17 variant alleles are virtually absent in Chileans. CYP1A1*2A allele frequency (0.37) is similar to that of Caucasians and higher than that reported for Japanese people. Allele frequencies for CYP3A5*3 (0.76) and CYP2C9*3 (0.04) are similar to those observed in Japanese people. CYP1A1*2C (0.32), CYP1A2*1F (0.77), CYP3A4*1B(0.06), CYP2D6*2(0.41) and MTHFR T(0.52) allele frequencies are higher than the observed either in Caucasian or in Japanese populations. Conversely, CYP2C19*2 allele frequency (0.12) and GSTT1null (0.11) and GSTM1null (0.36) genotype frequencies are lower than those observed in both populations. Finally, allele frequencies for CYP2A6*4(0.04), CYP2C8*3(0.06), CYP2C9*2(0.06), CYP2D6*4(0.12), CYP2E1*5B(0.14), CYP2E1*6(0.19), and UGT2B7*2(0.40) are intermediate in relation to those described in Caucasian and in Japanese populations, as expected according to the ethnic origin of the Chilean population. In conclusion, our findings support the idea that ethnic variability must be considered